Possibilities of using indirect free cooling in selected Polish cities - Zając, Agnieszka (Instal, 2025)
The need to reduce air pollution and prevent climate change influences decisions to implement the cleanest possible technologies in almost every area of life. Many of the recently published directives, KPE announcements and recovery plans concern changes and actions in the construction and installation sector. It is here that the share of approximately 35% in CO2 emissions and the same share in global energy consumption is noticeable. Top-down recommendations include increasing the use of natural and renewable energy sources in technical equipment installations for buildings at the expense of abandoning fossil fuels. One possibility is to use outdoor air energy for passive cooling in indirect installations operating for the needs of ventilation and air conditioning systems, which is described in the article below. For selected locations in Poland, graphs were prepared illustrating the potential of using free cooling at various operating temperatures of the installation used year-round and during the summer season from April to September during selected daytime hours. Criteria that influence the validity of using passive free cooling were also presented.